Replicating "State Action to Prevent Violence against Women". A Comment on Córdova & Kras (2022) - Synøve N. Andersen; Nicolai T. Borgen; Solveig T. Borgen; Elisa Brini; Michael J. Frith; Alexi Gugushvili (Institute for Replication (I4R), 2023)
Córdova and Kras (2022) examine how the existence of a women's police station (WPS) in the place of residence influences citizens' attitudes toward gender-based violence in Brazil. In their analytical specification, the authors find that men are more likely to reject violence against women (VAW) and support bystander intervention in municipalities with a WPS, especially if the WPS has been operating for a long time. This paper examines the replicability and robustness of Córdova & Kras' (2022) findings. First, we reproduce the paper's main findings and uncover one minor coding error and three estimates that have been reported with the opposite sign compared to that in our reproduction; neither is of consequence for the study's main results. Second, we test the robustness of the results by (1) recoding one of the main explanatory variables and several of the control variables to account for non-linear trends, (2) using alternative techniques to estimate clustered standard errors, (3) consistently applying a 95% confidence level in the presentation of the results, (4) altering the propensity score matching (PSM) procedure as well as the composition of the variables used in the PSM robustness check, (5) using an alternative technique to test for multicollinearity, (6) excluding potential endogenous control variables, and (7) using an alternative coding for computing margins. Reassuringly, the results are robust to most of these tests. However, two of the robustness checks challenge parts of the paper's main findings. First, allowing for non-linearity in the effect of time since the establishment of WPS shows (a) a non-linear effect on VAW and (b) no apparent changes in either male or female attitudes over time once the WPS has been established. Second, the inclusion of other variables in the PSM procedure renders part of the main estimates of interest statistically nonsignificant (p<0.1). Our findings highlight the need for further re-analyses and replications for investigating the preventive effects of women's police stations.
Keywords: 330